La adopción homo parental; y la vulneración de los derechos de los menores a tener una familia - Lucio Guerrero, Digna Isabel (2025)
This research will be carried out based on the following topic; Homo PARENTAL Adoption and the Violation of the rights of minors to have a family, carrying out a normative and doctrinal analysis on the legal institution of homo parental adoption in Comparative Law, considering the normative contradictions and legal gaps existing within our legal system, because at present, same-sex couples cannot carry out the adoption process, in this way many children who are in homes or known as orphanages, cannot have a stable home full of affection, Of emotional, economic stability, in which it can meet all the needs of the child, this would be one of the first considerations towards a violation of children's rights to develop in a home without caring or discriminating against their formation as a family. According to the supreme rule, the Constitution of the Republic of Ecuador in its article 68, states that the legal institution of adoption will correspond only to couples of different sexes, that is, that couples who are made up of the same sex cannot access the adoption procedures, it is worth mentioning that Ecuador is a Constitutional State of Rights and Justice itself that within its legal body guarantees the protection of rights, some of these being equality, freedom, and above all non-discrimination, historically and even to the present the right of Adoption is a limited right, granting only exclusive access to heterosexual couples, based on the conviction of the traditional family model, based on different conservative premises, the same ones that directly violate the rights of couples made up of people of the same sex.